2023
DOI: 10.1088/1755-1315/1142/1/012036
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of solar powered refrigerator in Uzbekistan climate

Abstract: The energetic performance of autonomous solar powered refrigerator is analyzed. In this refrigerator, the solar energy is converted into electrical energy by a photovoltaic (PV) array, then the generated electrical energy is used to power a vapor – compression system which produces cooling energy at its evaporator. The evaporator is sunk to the water so that produced cooling energy is used to formation water ice, thus accumulates cooling energy in the form of ice. While, compressor is working during the daylig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Technoeconomic optimization using HOMER software demonstrated that R152a exhibited superior performance and lower levelized cost of electricity compared to other refrigerants, making it a viable option for off-grid vaccine storage. Abdullaev et al 10 analyzed the energetic performance of an autonomous solar-powered refrigerator that utilized a PV array to generate electrical energy, which was then used to power a vapor-compression system. Cooling energy was stored in the form of ice during the daytime and utilized at night.…”
Section: Introductionmentioning
confidence: 99%
“…Technoeconomic optimization using HOMER software demonstrated that R152a exhibited superior performance and lower levelized cost of electricity compared to other refrigerants, making it a viable option for off-grid vaccine storage. Abdullaev et al 10 analyzed the energetic performance of an autonomous solar-powered refrigerator that utilized a PV array to generate electrical energy, which was then used to power a vapor-compression system. Cooling energy was stored in the form of ice during the daytime and utilized at night.…”
Section: Introductionmentioning
confidence: 99%